2010
DOI: 10.1029/2010gl043199
|View full text |Cite
|
Sign up to set email alerts
|

Effect of latitude on the persistence of eddy‐driven jets

Abstract: [1] An asymmetry in the persistence of the eddy-driven jet is demonstrated, whereby the equatorward-shifted (low-phase) jet is more persistent than the poleward-shifted (high-phase) jet. The asymmetry is investigated by stirring the nondivergent vorticity equation on the sphere and is shown to arise due to the sphericity of the earth, which inhibits poleward wave breaking when the jet is at high latitudes. This spherical effect becomes increasingly important as the mean jet is positioned at higher latitudes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
126
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(149 citation statements)
references
References 11 publications
20
126
3
Order By: Relevance
“…The life cycle of regime C (Figure 13, top row) is about 10 days and is of the order of 14 and 8 days for S ( Figure 13, middle row), and N ( Figure 13, bottom row) respectively. Thus regime N seems to be the least persistent, in agreement with Barnes and Hartmann (2010) and Barnes et al (2010). As is shown later, these transition paths are not inconsistent with the transition probabilities computed within the PC space.…”
Section: Patterns Of Growth/decay and Preferred Transition Pathssupporting
confidence: 63%
See 2 more Smart Citations
“…The life cycle of regime C (Figure 13, top row) is about 10 days and is of the order of 14 and 8 days for S ( Figure 13, middle row), and N ( Figure 13, bottom row) respectively. Thus regime N seems to be the least persistent, in agreement with Barnes and Hartmann (2010) and Barnes et al (2010). As is shown later, these transition paths are not inconsistent with the transition probabilities computed within the PC space.…”
Section: Patterns Of Growth/decay and Preferred Transition Pathssupporting
confidence: 63%
“…When the leading three PCs are used then we see that the largest persistence is obtained with regime C (although a little less stationary than the others), which can be broadly identified with the basic state (WO10b). The next persistent jet position is regime S or Greenland blocking, a well-known persistent feature (Barnes and Hartmann, 2010;Barnes et al, 2010). Interestingly, the persistence of the southern and northern jet positions has decreased significantly compared to the previous case.…”
Section: Transition Probabilities Between Jet Stream Positionsmentioning
confidence: 78%
See 1 more Smart Citation
“…The fact that the relationship is manifest acrossthe broad range of models suggests that it is robust, although as we might expect the relationship is less clean in comprehensive GCMs. The relationship has been implicitly noted by , who found that the latitudinal width of the momentum flux convergence was broader for jets located towards the pole in the simplified GCM, and by Barnes et al [2010] who found similar results in a stirredbarotropic model. The response is noticeably weaker in the barotropic model than the GCMs.…”
Section: Resultsmentioning
confidence: 51%
“…The response of the wave fluxes of momentum to a given forcing can arise through two sets of processes: 1) Through changes in the characteristics for meridional wave propagation aloft (i.e., via barotropic processes). For example, changes in the upper-tropospheric mean flow influence the direction of wave propagation into the stratosphere (e.g., Chen and Robinson 1992;Simpson et al 2009), the phase speed and critical latitudes for meridionally propagating waves (e.g., Chen and Held 2007;Chen et al 2008), the barotropic stage of the life cycle of baroclinic waves (Wittman et al 2007), and the geometry of the critical latitudes on the poleward and equatorward flanks of the jet (e.g., Chen and Zurita-Gator 2008; Barnes et al 2010;Kidston and Vallis 2012). 2) Through changes in the growth of wave activity in the troposphere (i.e., via baroclinic processes).…”
Section: Introductionmentioning
confidence: 99%